Wana Alus Sebagai Ruang Sakral: Telaah Filsafat dan Agama Atas Misteri Kemah Terlarang di Dusun Pencu - Mu'minin, Nashrul (LP2M Universitas Ibrahimy, 2026)
Wana Alus in Pencu Hamlet, Terong Village, Dlingo District, Bantul, is a forest area steeped in mystical narratives and religious practices that live on in the community's collective memory. Its popularity has surged again after its local stories were featured in the film *Kemah Terlarang*, which positioned the forest as both a mysterious space and a symbol of spirituality. This research begins with the central problem of the conflict of meaning between belief in supernatural entities and more rational religious understanding, and how this influences the community's treatment of Wana Alus as a sacred space. The purpose of this study is to explain the construction of religious meaning attached to Wana Alus, analyze the perspective of religious philosophy on this local sacred space, and evaluate the relevance of spiritual values ​​emerging from local community narratives. This research employed a descriptive qualitative approach, employing literature review, narrative analysis, and secondary data collection in the form of documentation of folktales, local historical records, and in-person interviews collected from credible sources. The analysis employed religious phenomenology and sacred space hermeneutics to understand the structure of the community's experience of Wana Alus. The results indicate that this forest is not only perceived as a place of horror, but also as an ethical, spiritual, and ecological space that regulates social behavior, morality, and respect for nature. The discussion emphasized that Wana Alus is a concrete example of how myth, religiosity, and philosophy about transcendent space intersect in rural community culture.